Assessing the influence of fibre type and biofilms on the ingestion and retention of microfibres by freshwater invertebrates - Evans, Isobel (2025)
Microfibre pollution is an escalating environmental issue, with natural fibres found in greater abundance than their synthetic counterparts in the environment. This study examines the ingestion and retention of microfibres by two freshwater macroinvertebrates, Gammarus pulex and Corbicula fluminea, under varying conditions of fibre type, biofilm presence, water turbidity, and exposure time. Ecotoxicity tests revealed significant ingestion of both polyester and cotton microfibres, with species-specific retention and ingestion patterns that differed with fibre type. For G. pulex, polyester fibres exhibited longer retention, while cotton fibres were ingested in larger quantities. The presence of biofilms enhanced fibre ingestion, indicating a key role in retention. Notably, G. pulex continued ingesting microfibres over one- and two-week exposure periods, suggesting no learning avoidance of microfibre consumption. C. fluminea ingested consistently low number of microfibres throughout all experiments, suggesting that selective feeding mechanism of suspension feeding bivalves may limit the risk of microfibre ingestion. These findings underscore the environmental risks posed by both natural and synthetic microfibres and highlight the need for further research, particularly on natural fibres, to assess their ecological impacts at environmentally relevant concentrations.